Contrast Enhanced Transabdominal Ultrasound in the Characterisation of Pancreatic Lesions with Cystic Appearance - Beyer-Enke, Stefan A; Hocke, Michael; Ignee, Andre; Braden, Barbara; Dietrich, Christoph F (JOP. Journal of the Pancreas, 2010)
Context Contrast enhanced ultrasound (CEUS) has been established for detection and characterisation of liver tumours and differential diagnosis of solid pancreatic lesions. The role of transabdominal CEUS in cystic pancreatic disease is less obvious. Objective We prospectively evaluated CEUS for characterization of undetermined cystic pancreatic lesions with respect to the differential diagnosis of pseudocysts and cystic neoplasia and differentiation between benign and malignant disease (gold standard: histology or cytology). Patients One-hundred and fourteen patients (63 males, 51 females; median age: 62 years, range: 33-87 years) were prospectively examined. Investigations Conventional B-mode and transabdominal CEUS. Main outcome measures Conventional B-mode (criteria: solid nodules, septae), and contrast enhancing features of cystic pancreatic lesions (microperfusion of solid nodules) were analysed. Final diagnoses were made by surgery (47 patients) or histology/cytology and follow-up of at least one year (67 patients). Results Fifty patients proved to have neoplastic lesions (37 malignant, 13 of benign origin). Sixty-four patients had pseudocysts caused by acute (27 patients) or chronic pancreatitis (37 patients). Conventional B-mode had a sensitivity of 94% and a low specificity of 44% in the differentiation of pseudocysts versus neoplasia. CEUS had a higher specificity of 77% with the same sensitivity of conventional B-mode ultrasound. The combination of conventional ultrasound and CEUS improved the specificity even more to 97% with an unchanged sensitivity. CEUS was not reliable in the differentiation of benign and malignant neoplasia. Conclusion CEUS improves the differentiation between pseudocysts and pancreatic neoplasia in comparison to the conventional B-mode imaging. The microvascularisation visualised using CEUS even in small nodules (with or without septae) associated with cystic lesions is an indicator for cystic pancreatic neoplasia. Image: CEUS in a patient with mucinous cystadenoma.